Analisis Perbandingan Penerimaan Pajak Kendaraan Bermotor Sebelum Dan Di Masa Pandemi Covid-19 Dan Kontribusinya Terhadap Penerimaan Pendapatan Asli Daerah Provinsi Jawa Barat - Falisha Laylani Amelia Putri; Susilawati (Indonesian Journal of Applied Accounting and Finance, 2023)
The Covid-19 pandemic that struck Indonesia forced the government to struggle to keep the economy running amidst limitations. Economic activity that is not fully functioning causes West Java Province’s tax revenue to decline. One type of local tax in West Java Province that has experienced a decline in revenue is the Vehicle Tax. From 2015 to 2021, Vehicle Tax still has the largest contribution to Regional Tax Revenue in West Java Province’s. This research is a quantitative study using the comparison method. The data used in this study are secondary data, namely the target and realization of vehicle tax revenue, and the realization of Regional Original Revenue of West Java Province for the 2018-2021 period. The comparison test, or hypothesis test, in this study is the Wilcoxon test. The results of this study indicate that there is a significant difference between Vehicle Tax Revenue before and during the Covid-19 pandemic. There is also a significant difference between the contribution of Vehicle Tax to local revenue before and during the Covid-19 pandemic